Biomarker Discovery in Atherosclerotic Diseases Using Quantitative Nuclear Magnetic Resonance Metabolomics - Ma, Shuai; Xia, Mingfeng; Gao, Xin (Frontiers in Cardiovascular Medicine, 2021)
Despite great progress in the management of atherosclerosis (AS), its subsequent cardiovascular disease (CVD) remains the leading cause of morbidity and mortality. This is probably owing to insufficient risk detection using routine lipid testing, thus prompting more effective approaches relying on new biomarkers. Quantitative Nuclear Magnetic Resonance (qNMR) metabolomics is able to phenotype the holistic metabolic changes, with a unique advantage in quantifying lipid-protein complex. The rapid increasing literature has indicated that qNMR-based lipoprotein particle number, particle size, lipid components, as well as some molecule metabolites can provide a deeper insight into atherogenic diseases, serving as novel promising determinants. Therefore, this article aims to offer an updated review of qNMR biomarkers of AS and CVD found in epidemiological studies, with a special emphasis on lipoprotein related parameters. With further researches in the future, we can envision more qNMR metabolite biomarkers successfully translated into daily clinical practice to enhance prevention, detection and intervention of atherosclerotic diseases.